Prospective observational study evaluating association of sociodemographic parameters, Wagner’s grading, peripheral arterial disease and diabetic peripheral neuropathy with the outcomes of diabetic foot ulcers - Ravidas, Vishnu S.; P., Samadarsi; G., Ajayan (International Surgery Journal, 2020)
Background: The present study was conducted to determine the association of sociodemographic parameters, comorbid conditions and complications of diabetes mellitus (DM) with the treatment outcomes of diabetic foot ulcers. Methods: The present prospective observational study enrolled 105 participants aged 30-85 years with diabetic foot ulcers presenting to general surgery department during a period of 18 months. Participants who were terminally ill, who had trophic ulcers of Hansen’s disease and filariasis and its sequelae were excluded. The study was approved by institutional ethics committee and written informed consent was obtained from all study participants. Data was analyzed using R and the test of significance was chi square test, p<0.05 was considered statistically significant. Results: Higher proportion of male participants and those aged between 50-69 years were encountered. Male participants were of higher age and the mean duration of DM in participants with diabetic foot ulcer was 8 years. The mean HbA1C of study participants was 8.1%, 38.1% participants had high plasma glucose. Food deformity was observed in 41% participants. 62.9% and 66.7% participants had diabetic peripheral neuropathy and peripheral arterial disease respectively. The mean time required for healing among participants with diabetic foot ulcers was 45.8 Significant association of major amputation with diabetic peripheral neuropathy (p=0.02), Wagner’s grading (p<0.001) and peripheral arterial disease (PAD) (p=0.006) was observed. Conclusions: The presence of diabetic peripheral neuropathy and PAD were risk factors for major amputations in diabetic foot ulcers. Lower Wagner’s grading was associated with lower chances of major amputation.